Global prevalence of urolithiasis: a meta-analysis accounting for methodological heterogeneity - Vera-Ponce, Víctor Juan; Sanchez-Tamay, Nataly Mayely; Ballena-Caicedo, Jhosmer; Zuzunaga-Montoya, Fiorella E.; De Carrillo, Carmen Inés Gutierrez; Poemape Mestanza, Rossmery Leonor (Frontiers in Urology, 2025)
IntroductionUrolithiasis, also known as renal lithiasis or nephrolithiasis, is an increasingly relevant urological pathology worldwide.ObjectiveTo estimate the global prevalence of urolithiasis through a systematic review (SR) with meta-analysis, and to systematically investigate methodological sources of heterogeneity in reported prevalence, including differences according to diagnostic methods, sex, and geographical regions.MethodologyA SR followed PRISMA guidelines adapted for prevalence studies, searching SCOPUS, Web of Science, PubMed, and EMBASE. Observational studies were included in reporting the frequency of urolithiasis diagnosed by ultrasound, tomography, or self-report. A meta-analysis of proportions was performed using a random-effects model with double arcsine transformation. Subgroup analyses by diagnostic method, sex, sampling strategy, and geographical region were conducted. Additionally, meta-regression was conducted to analyze the influence of publication year on prevalence.ResultsIn the combined analysis of 22 studies encompassing 1, 276, 826 participants, the estimated global prevalence of urolithiasis was 10.85% (95% CI: 8.76–13.14%). Considerable heterogeneity was observed (I² = 100%). Subgroup analyses revealed that diagnostic methods substantially influenced estimates: ultrasound 8.71% (95% CI: 5.74–12.23%), computed tomography 7.83% (95% CI: 7.12–8.60%), and self-report 13.28% (95% CI: 9.98–16.98%). Probabilistic sampling yielded 8.59% (95% CI: 6.34–11.14%) versus non-probabilistic 12.24% (95% CI: 9.32–15.50%). Prevalence was higher in males (12.93%) than females (8.91%). Regional variation ranged from 22.3% (Africa) to 8.3% (North America). Meta-regression showed publication year had no significant effect when adjusted for methodological factors (p = 0.1304).ConclusionsUrolithiasis affects approximately 11% of the global population, constituting a public health problem requiring comprehensive preventive, diagnostic, and therapeutic actions. The substantial heterogeneity is largely explained by methodological factors, particularly diagnostic methods and sampling strategies. This highlights the critical importance of standardizing diagnostic and recruitment criteria to obtain comparable measurements for guiding health policies and future research.